Analysis of Physical Condition Futsal Players at Senior High School Islam Sabilillah Malang City - Fery, Fery Mardianto; Sari, Reno Siska; Aris, Tria Muhamad (Universitas Singaperbangsa Karawang, 2024)
This article aims to find out and analyze data about the physical condition of the Sabilillah Islamic High School Malang futsal players. The method used is a quantitative method with a descriptive approach. The sampling technique uses total sampling where the sample is the same as the population, so that the sample used is all futsal players at Sabilillah Islamic High School Malang, totaling 15 people. The results of the research showed that the average score for the players' physical condition in the endurance test with the balke test was 53.19 in the moderate category, the speed test with the 30 meter running test averaged 4.54 in the poor category and the agility test tested with the T-test averaged average 10.9 in the medium category. The percentage results in the endurance test with the walking test produced a figure of 66.60% in the moderate category, the speed test with the 30 meter running test produced a figure of 46.60% in the poor category and the agility test tested with the T-test showed a figure of 73.30% in the moderate category. By analyzing the physical condition of futsal players, coaches can develop training programs designed to improve the physical aspects that need improvement. Keywords: Analysis, Physical Condition, Futsal Players